Paciente masculino de 16 años diagnosticado con aniseiconia y problema funcional. - Gómez Argoti, Dara Imano (2020)
The present clinical case that is revealed is a patient with a diagnosis of aniseiconia related to high myopia, astigmatism and a functional problem (amblyopia). Aniseiconia is the condition of binocular vision in which there is a relative difference in the size and / or shape of the eye images. The importance of early detection of these visual alterations has to do with a series of symptoms that the patient reports such as: frowning, blurred vision, head tilt, head turning, headache, nausea, dizziness, sleep among others. The objective of the research is to identify the etiology of anisoiconia and the functional problem that causes visual disturbance. The applied methodology is based on the analysis of the clinical history of the patient where he presented visual acuity without correction of RE = 20/100 LE = 20/200 after two years at the time of being evaluated with objective examinations such as: autorefractometer, retinoscopy , subjective as: phoropter and complementary as: ophthalmoscopy, biomicroscopy, keratometry, a significant increase in visual acuity without correction could be verified with a result of OD = 20/200 LE = 20/400 that served to make a definitive diagnosis and prescribe adequate treatment. In the ophthalmoscopic examination, this patient presented the transparent refractive media, the slightly enlarged optic disc typical of a high myopia within the disc cup ratio, the patient has a disc cup ratio of 0.3 equivalent to a normality according to the standardization (RECA). The conclusion of the study is that anisometropia and aniseiconia can be confused, but represent a different problem, although both can lead to the appearance of amblyopia or lazy eye.